2011
DOI: 10.1254/jphs.10276fp
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Docetaxel on Platelet-Derived Growth Factor (PDGF)-BB–Induced Proliferation of Vascular Smooth Muscle Cells Through Blocking PDGF-Receptor β Phosphorylation

Abstract: Abstract. The abnormal proliferation of vascular smooth muscle cells (VSMCs) in arterial wall is an important pathogenic factor for vascular disorders such as atherosclerosis and restenosis after angioplasty. The present study was designed to investigate the inhibitory effects of docetaxel on VSMC proliferation, as well as the molecular mechanism of this inhibition. Docetaxel at 10, 20 and 40 μM significantly inhibited both the proliferation and the DNA synthesis of fetal bovine serum (FBS)-and platelet-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 52 publications
(41 reference statements)
1
24
0
2
Order By: Relevance
“…Despite these advancements, today's DES have not completely eradicated restenosis and still lead to a higher incidence of late stent thrombosis. Drug docetaxel (DTX) is a paclitaxel analogue with enhanced anti-proliferative ability and water solubility and has been shown to be a good candidate drug for the prevention of restenosis 9,10 . Thrombosis remains a concern after stent implantation, whether at the early or very late stage.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advancements, today's DES have not completely eradicated restenosis and still lead to a higher incidence of late stent thrombosis. Drug docetaxel (DTX) is a paclitaxel analogue with enhanced anti-proliferative ability and water solubility and has been shown to be a good candidate drug for the prevention of restenosis 9,10 . Thrombosis remains a concern after stent implantation, whether at the early or very late stage.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the same concept, imatinib and carboplatin have enhanced efficiency in suppressing VEGF, PDGF and PDGF-Rα/ß expression in head and neck squamous cell carcinoma [90,91]. Docetaxel has been currently acclaimed as an inhibitor of PDGF; however, there are controversial findings, and future research is necessary to unveil opportunities and challenges in the standardization of therapy [92,93]. Bevacizumab has been used in combination with (PDGF aptamer, AX102) and displayed therapeutic efficacy [94].…”
Section: Pdgf As a Major Challenge In Translational Oncologymentioning
confidence: 88%
“…In this study, stents with ADC may be an alternative solution for this problem. Anti-proliferative drugs DTX which can significantly inhibited the proliferation of VSMCs in a concentration-dependent manner 22 are only coated on the outer surface of stents to suppress neointima hyperplasia, while antithrombotics SZ-21which can bind platelet glycoprotein IIIa and inhibit platelet aggregation 23 coated on inner surface of stents may inhibit thrombus formation. Since endothelium could completely cover the inner surface of stent as early as possible, it will then decrease the possibility of ISR.…”
Section: Discussionmentioning
confidence: 99%
“…In the other aspect of anti-proliferation, DTX cumulative release has reached 18 mg/mL (approximately 20 μM) within 24 h and became the main release drug from 24 h to 7 d, which shows that ADC can significantly inhibit the proliferation of VSMCs. Because 10 μM docetaxel can significantly inhibit both the proliferation and the DNA synthesis of fetal bovine serum and plateletderived growth factor-BB-stimulated VSMCs in a concentration-dependent manner 22 . And in vitro cell proliferation assay, the PDC and ADC could significantly reduce VSMCs proliferation compared to the 316L SS stents after 3 d or 5 d co-culture, which indicated that DTX can potentially inhibit intimal hyperplasia and ISR caused by excessive VSMCs proliferation, migration to the intima and secretion of large amounts of extracellular matrix protein.…”
Section: Discussionmentioning
confidence: 99%